Environment and air pollution like gun and bullet for low-income countries: war for better health and wealth - Zou, Xiang; Azam, Muhammad; Islam, Talat; Zaman, Khalid (Springer Berlin Heidelberg, 2016)
The objective of the study is to examine the impact of environmental indicators and air pollution on “health” and “wealth” for the low-income countries. The study used a number of promising variables including arable land, fossil fuel energy consumption, population density, and carbon dioxide emissions that simultaneously affect the health (i.e., health expenditures per capita) and wealth (i.e., GDP per capita) of the low-income countries. The general representation for low-income countries has shown by aggregate data that consist of 39 observations from the period of 1975–2013. The study decomposes the data set from different econometric tests for managing robust inferences.The study uses temporal forecasting for the health and wealth model by a vector error correction model (VECM) and an innovation accounting technique.The results show that environment and air pollution is the menace for low-income countries’ health and wealth. Among environmental indicators, arable land has the largest variance to affect health and wealth for the next 10-year period, while air pollution exerts the least contribution to change health and wealth of low-income countries.These results indicate the prevalence of war situation, where environment and air pollution become visible like “gun” and “bullet” for low-income countries.There are required sound and effective macroeconomic policies to combat with the environmental evils that affect the health and wealth of the low-income countries.